2017
DOI: 10.1108/sbm-02-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding strategic decision-making through a multi-paradigm perspective

Abstract: 1 Understanding strategic decision-making through a multi-paradigm perspective: The case of charitable foundations in English football AbstractPurpose: The purpose of this paper is to illustrate the efficacy of using a multi-paradigm perspective to examine the relationship between CSR and strategic decision-making processes in the context of charitable foundations. Findings:The present study illustrates empirically that strategic decision-making in charitable foundations does not 'seat' neatly in any one of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…Conversely, Lewicki and Bunker (1996, p. 122) referred in 'identification-based trust' to an identity common to both parties (trustor and trustee) in which 'each can represent the other's interests with their full confidence' (Dietz and Hartog, 2006, p. 564). However, in the present context, and as recent studies have shown (Anagnostopoulos et al, 2017;Kolyperas et al, 2016), a sort of dysfunctional affiliation between the foundations and the 'parent' teams exists that requires manoeuvring (see Anagnostopoulos et al, 2014) to move closer to what trust literature refers to as identification-based trust.…”
Section: On the Role Of Trustmentioning
confidence: 77%
See 3 more Smart Citations
“…Conversely, Lewicki and Bunker (1996, p. 122) referred in 'identification-based trust' to an identity common to both parties (trustor and trustee) in which 'each can represent the other's interests with their full confidence' (Dietz and Hartog, 2006, p. 564). However, in the present context, and as recent studies have shown (Anagnostopoulos et al, 2017;Kolyperas et al, 2016), a sort of dysfunctional affiliation between the foundations and the 'parent' teams exists that requires manoeuvring (see Anagnostopoulos et al, 2014) to move closer to what trust literature refers to as identification-based trust.…”
Section: On the Role Of Trustmentioning
confidence: 77%
“…According to the reciprocity principle, it is expected the trustee will not abuse the trustor as they give direct or indirect benefits to one another (Lévi-Strauss, 1969;Molm et al, 2007). For example, the 'parent' team supports its charitable foundation with financial and/or contributions-in-kind with the view that the latter will juxtapose a positive image in the community where the former exists and operates (Anagnostopoulos et al, 2017;Kolyperas et al, 2016).…”
Section: Reciprocal Trust Relationship and Social Exchange Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…As might be expected, given football's transition, these clubs have been a source of significant empirical evaluation. However, there has been a tendency to explore them through various managerial lenses (Anagnostopoulos, Byers, & Kolyperas, 2017; Reid, 2017) and to study their impact on the pillars of SE. These pillars have been identified as wellbeing, mental health enhancement, and support (Henderson, O'Hara, Thornicroft, & Webber, 2014) and community education.…”
Section: Review Of the Literaturementioning
confidence: 99%